Therapeutic potential of natural products in ischemic stroke: targeting angiogenesis - Li, WenQiang; Liu, E.; Zhou, YiHao; Liao, ZhiChao; Wang, DongYan (Frontiers in Pharmacology, 2025)
Ischemic stroke (IS), a leading global cause of mortality and long-term disability, necessitates immediate intervention for eligible patients. Current guidelines mandate intravenous thrombolysis within 4.5 h of symptom onset for individuals without contraindications, achieving vessel recanalization rates up to 85% in treated cohorts. However, therapeutic time windows may extend to 4.5–24 h for select patients when guided by advanced multimodal imaging (CT perfusion or diffusion-weighted MRI) to identify salvageable penumbral tissue. While revascularization remains the cornerstone of acute IS management, emerging evidence underscores angiogenesis as a critical biological process for neurovascular repair and functional recovery during the subacute-to-chronic phases. Natural products (NPs), have demonstrated multiple advantages in the treatment of IS, including multi-target modulation, relatively easy access to raw materials, relatively low price, and the significant advantage of having wide selectivity offer novel opportunities for addressing these limitations. This review systematically analyses 13 major NPs classes including saponins, terpenoids, cycloenol ether terpene glycosides, flavonoids, ketones and macrocycles, phenolic acids, phenylpropanoids, polysaccharides, phenolphthaleins, complexes/extracts, volatile oils, alkaloids, and polymeric materials complexes class of compounds, We elucidate the molecular cascade in which NPs regulate the hypoxia-inducible factor 1α (HIF-1α)/Vascular endothelial growth factor (VEGF), Notch and Wnt/β-catenin signaling pathways to promote vascular regeneration. In particular, our study focuses on the critical role of angiogenesis during the development of IS, highlighting that NPs can enhance neovascularization by alleviating oxidative stress/inflammation, among other pathways. These insights offer translational possibilities for the development of NP-based combination therapies targeting both the acute neuroprotective and chronic recovery phases.